Treatments for hyperemesis gravidarum: A systematic review - Marie‐Therese Vinnars; Maria Forslund; Ing‐Marie Claesson; Annicka Hedman; Nathalie Peira; Hanna Olofsson; Emma Wernersson; Hanna Ulfsdottir (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Hyperemesis gravidarum affects 0.3%–3% of pregnant women each year and is the leading cause of hospitalization in early pregnancy. Previous systematic reviews of available treatments have found a lack of consistent evidence, and few studies of high quality. Since 2016, no systematic review has been conducted and an up‐to date review is requested. In a recent James Lind Alliance collaboration, it was clear that research on effective treatments is a high priority for both patients and clinicians. Material and methods Searches without time limits were performed in the AMED, CINAHL, Cochrane Library, EMBASE, Medline, PsycINFO, and Scopus databases until June 26, 2023. Studies published before October 1, 2014 were identified from the review by O'Donnell et al., 2016. Selection criteria were randomized clinical trials and non‐randomized studies of interventions comparing treatment of hyperemesis gravidarum with another treatment or placebo. Outcome variables included were: degree of nausea; vomiting; inability to tolerate oral fluids or food; hospital treatment; health‐related quality of life, small‐for‐gestational‐age infant; and preterm birth. Abstracts and full texts were screened, and risk of bias of the studies was assessed independently by two authors. Synthesis without meta‐analysis was performed, and certainty of evidence was assessed using the GRADE approach. PROSPERO (CRD42022303150). Results Twenty treatments were included in 25 studies with low or moderate risk of bias. The certainty of evidence was very low for all treatments except for acupressure in addition to standard care, which showed a possible moderate decrease in nausea and vomiting, with low certainty of evidence. Conclusions Several scientific knowledge gaps were identified. Studies on treatments for hyperemesis gravidarum are few, and the certainty of evidence for different treatments is either low or very low. To establish more robust evidence, it is essential to use validated scoring systems, the recently established diagnostic criteria, clear descriptions and measurements of core outcomes and to perform larger studies.